Plastic collapse load numerical evaluation of welded beam-to-column steel joints. (December 2017) - Fuschi, P.; Pisano, A.A.; Pucinotti, R.
Abstract: A finite element based numerical procedure for predicting the plastic collapse load as well as the plastic collapse mechanism of beam-to-column steel joints is presented. The promoted procedure is based on two methods following the static and the kinematic approach of limit analysis. Both methods have been rephrased for a von Mises type material in the deviatoric plane and in terms of deviatoric stress invariants. The key concepts are: i) in the static formulation, to mimic the stress redistribution arising within a structure approaching its critical (collapse) state, such stresses being in equilibrium with the maximum redistributable loads; ii) in the kinematic formulation, to build a plastic collapse mechanism characterized by compatible strain and displacement rates corresponding to a minimum value of loads doing positive work equal to the total plastic dissipation. A validation of the numerical results is pursued by comparison with experimental findings on real scale prototypes of the tackled steel joints. Future developments are outlined at closure. Highlights: Plastic collapse load prediction of beam-to-column steel joints Finite element procedures for limit analysis Validation by numerical simulation of experimental tests on large-scale prototypes